Theory of Communication in Gorgias and Plato’s Cratylus - Adomėnas, Mantas (Literatūra, 2025)
This essay attempts to establish a link between the third part of the Περὶ τοῦ μὴ ὄντος that contains Gorgias’ critique of communication and Plato’s theory of communication (as developed in the Cratylus). After analysing the text of, and attempting to reconstruct the original structure of Gorgias’ argument in, Part 3 of the Περὶ τοῦ μὴ ὄντος, the author contends that Plato, in spite of never addressing Gorgias’ work directly, formulates his theory of communication in the Cratylus within the conceptual schemes present in Gorgias’ treatise. Plato implicitly criticises Gorgias’ refutation of the possibility of communication, while retaining, nevertheless, certain features of Gorgias’ argument.